2003
DOI: 10.1002/jbm.a.10472
|View full text |Cite
|
Sign up to set email alerts
|

Determination of specific interactions between glucose ligand carrying polymer and glucose transporter type‐1 (GLUT‐1) using different cell types

Abstract: Abstract:In order to develop a biomimetic polymer for cell recognition, poly [3-O-(4Ј-vinylbenzyl)-D-glucose] (PVG) and different types of glucose transport (GLUT)-carrying cells, namely, HepG2 cells (GLUT-1), 3T3-L1 fibroblast cells (GLUT-1 and GLUT-4), and MIN6 cells (GLUT-2), were tested for specific interaction. To clarify the nature of interaction between PVG and the different cell types, rhodamine-B isothiocyanate (RITC)-labeled polymers were used to prove and visualize the interactions. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The presence of galactose in GS-Lx sponges could be responsible for the observed morphology and higher density of cytoskeletal filaments, facilitating the asialoglycoprotein-mediated cell adhesion of HepG2 cells [ 52 , 53 , 54 ]. Spreading of cells on GS-Lx demonstrated an improved cell–matrix interaction, while on GS-Mx sponges the spherical morphology of the HepG2 cells suggested a different anchoring to the scaffold, probably due to the presence of the type-1 glucose transporter (GLUT-1) receptor [ 55 ]. GLUT-1 is highly expressed also in chondrocytes [ 56 ] and could be involved in cell-scaffold interactions in glucose-carrying scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of galactose in GS-Lx sponges could be responsible for the observed morphology and higher density of cytoskeletal filaments, facilitating the asialoglycoprotein-mediated cell adhesion of HepG2 cells [ 52 , 53 , 54 ]. Spreading of cells on GS-Lx demonstrated an improved cell–matrix interaction, while on GS-Mx sponges the spherical morphology of the HepG2 cells suggested a different anchoring to the scaffold, probably due to the presence of the type-1 glucose transporter (GLUT-1) receptor [ 55 ]. GLUT-1 is highly expressed also in chondrocytes [ 56 ] and could be involved in cell-scaffold interactions in glucose-carrying scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…HEp-2 cell adhesion was tested on the polymer films dip-coated on glass slides with a size of 10 × 10 mm 2 . HEp-2 cells were routinely cultured in T-75 culture flasks containing 10–12 mL of AMEM, 10% (v/v) FBS, and 0.5% (v/v) l -glutamax at 37 °C under a humidified 5% carbon dioxide (CO 2 ) atmosphere as described in the literature. The film specimens were sterilized as described above, washed with DPBS, and placed in 6-well culture plates. HEp-2 cells were seeded onto the films at a density of 0.3 × 10 6 cells mL –1 (A660 = 0.10) and incubated for 6 days with a change of media every second day.…”
Section: Methodsmentioning
confidence: 99%
“…These data confirmed that the cellular uptake of the PLGA-Glc NPs was based on the interaction between the glucose moiety of the NPs and the GLUTs expressed in the cells, matching with a previous study that reported the specific interaction between a glucose ligand-carrying polymer and GLUT in cell lines. 41 GLUTs-mediated internalization of PLGA-Glc NPs implies the feasibility of its application in tumor-targeted drug delivery. The tumor microenvironment can be characterized by hypoxia, a low glucose concentration, and a high lactate concentration.…”
Section: In Vitro Cellular Uptakementioning
confidence: 99%